Porodní péče a zkušenosti českých žen: kvalitativní studie - Ema Hrešanová (Gender a Výzkum)
Focusing on Czech birth care, this article examines the birth experience of 40 women who gave birth in different maternity hospitals during the past seven years. It investigates how these women approached birth care and what ideas they had about it. The article builds on semi ‑structured and narrative interviews with postpartum women, which were conducted within two different research projects. The interviewees differed in many aspects and especially in their general approach to childbirth issues and their interest in the subject. Several key issues emerged out of the thematic analysis of interviews: fear of childbirth, birth care evaluations, priorities and demands, and strategies of their enforcement. These issues are part of a wider concept of birth care, and five different conceptions of birth care were identified in the women’s birth narratives. They reflect different attitudes to the medicalization of birth care, different levels of knowledge and interest in childbirth issues, and different perceptions of their own position in the context of care provision.